Kajian spasial autokorelasi penyebaran penyakit demam berdarah dengue di Kabupaten Karanganyar tahun 2017–2021 - Muhamamd Rasyid Bintang Abdulmajid (Journal of Health and Therapy, 2024)
Dengue Hemorrhagic Fever (DHF) cases in Karanganyar Regency from 2017 to 2021 fluctuated, with the highest number recorded at the Karanganyar Community Health Center (Puskesmas) and the lowest at the Jatipuro Community Health Center. This study aims to analyze the spatial pattern of DHF incidence in Karanganyar Regency. The study used a quantitative descriptive design and was conducted from February–April 2024 in the Karanganyar Regency Health Office's working area. The data used included DHF cases from 21 community health centers in 2017–2021, population, population density, and regional elevation. Spatial analysis was conducted using QGIS and GeoDa with the Local Indicator of Spatial Autocorrelation (LISA) method. The results showed that population density and regional elevation in 2017 and 2019–2021 exhibited spatial autocorrelation with a scattered pattern, whereas population in 2017–2021 and DHF cases in 2018 showed no spatial autocorrelation. The areas of Kebakkramat 1, Jaten 1, Jaten 2, Tasikmadu, and Karanganyar Health Centers have been identified as hotspots with a high risk of dengue fever transmission from the surrounding areas.